On the axial crush performance of PVC foam-filled aluminum/CFRP hybrid circular tube - Kenan Genel; Muhammet Muaz Yalçın (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi)
In this study, anexperimental investigation was carried out to improve the energy absorptioncapability of the circular aluminum tubes. For this purpose, different specimenconfigurations such as PVC foam-filled, empty hybrid (strengthened with CFRP)and PVC foam-filled hybrid tubes were prepared and tested under axialcompression. It is noted from the experiments that the contribution of foamfilling maximized when it was used with CFRP together. The results revealedthat energy absorption capacity (EAC) of the foam-filled hybrid tube was 2.7times of the base tube. Moreover, the specific energy absorption (SEA) valueenhanced almost 70% compared to that of the base tube and reached 34.9 J/gr.